AIP Conference Proceedings 2009
DOI: 10.1063/1.3149481
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Topological Insulators and Superconductors

Abstract: An exhaustive classification scheme of topological insulators and superconductors is presented. The key property of topological insulators (superconductors) is the appearance of gapless degrees of freedom at the interface/boundary between a topologically trivial and a topologically non-trivial state. Our approach consists in reducing the problem of classifying topological insulators (superconductors) in d spatial dimensions to the problem of Anderson localization at a (d-1) dimensional boundary of the system. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
479
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(483 citation statements)
references
References 6 publications
3
479
0
Order By: Relevance
“…Here, we caution that T and U are symmetries of the circle ðk y ∈ ½−π; π ; k ∥ Þ and preserve the momentum parameter k ∥ ; this differs from the conventional [23] time-reversal and particle-hole symmetries that typically invert momentum. To precisely state (iii), we first elaborate on how Wilson bands may be labeled by mirror eigenvalues, which we define as λ j for the reflectionM j (j ∈ fx; zg).…”
Section: A Local Rules Of the Curvesmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we caution that T and U are symmetries of the circle ðk y ∈ ½−π; π ; k ∥ Þ and preserve the momentum parameter k ∥ ; this differs from the conventional [23] time-reversal and particle-hole symmetries that typically invert momentum. To precisely state (iii), we first elaborate on how Wilson bands may be labeled by mirror eigenvalues, which we define as λ j for the reflectionM j (j ∈ fx; zg).…”
Section: A Local Rules Of the Curvesmentioning
confidence: 99%
“…The point group (D 6h ) of KHgX, defined as the quotient of its space group by translations, is generated by four spatial transformations-this typifies the complexity of most space groups. This work describes a systematic method to topologically classify space groups with similar complexity; in contrast, previous classifications [1,2,[4][5][6][7]14] (with one exception by us [8]) have expanded the Altland-Zirnbauer symmetry classes [22,23] to include only a single point-group generator. For point groups with multiple generators, different submanifolds of the Brillouin torus are invariant under different symmetries; e.g., mirror and glide planes are respectively mapped to themselves by a symmorphic reflection and a glide reflection, as illustrated in Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fermionic SPT states include the familiar quantum spin Hall (QSH) insulator [3,4], the three-dimensional (3d) topological insulator (TI) [5][6][7], and topological superconductors. Noninteracting fermionic SPT states have been fully classified and understood [8,9]. Unlike fermionic systems, bosonic SPT (BSPT) states require strong interaction to overcome the tendency to form Bose-Einstein condensates.…”
mentioning
confidence: 99%
“…They have been the subject of theories for more than seven decades without an experimental signature. However recently it has been suggested that these exotic particles can be discovered in condensed matters systems, in particular in topological superconductors (TSCs) [1][2][3][4][5][6][7][8] . TSCs are superconducting systems that admit exceptional boundary states -owing to nontrivial topology associated with bulk spectra-inside the quasi-particle excitation gaps.…”
Section: Introductionmentioning
confidence: 99%